2016
DOI: 10.1016/j.celrep.2016.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Programming of Intestinal Epithelial Differentiation by IL-33 Derived from Pericryptal Fibroblasts in Response to Systemic Infection

Abstract: The intestinal epithelium constitutes an efficient barrier against the microbial flora. Here, we demonstrate an unexpected function of IL-33 as a regulator of epithelial barrier functions. Mice lacking IL-33 showed decreased Paneth cell numbers and lethal systemic infection in response to Salmonella typhimurium. IL-33 was produced upon microbial challenge by a distinct population of pericryptal fibroblasts neighboring the intestinal stem cell niche. IL-33 programmed the differentiation of epithelial progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 60 publications
3
83
0
Order By: Relevance
“…Although they are less well characterized, non‐immune cells may also constitute important cellular targets of IL‐33 in vivo. These include endothelial cells, epithelial cells, fibroblasts, astrocytes, and neurons …”
Section: Activation Of St2‐expressing Cellsmentioning
confidence: 99%
“…Although they are less well characterized, non‐immune cells may also constitute important cellular targets of IL‐33 in vivo. These include endothelial cells, epithelial cells, fibroblasts, astrocytes, and neurons …”
Section: Activation Of St2‐expressing Cellsmentioning
confidence: 99%
“…This process is mediated by a well-established pathway in which intestinal stem cells from the crypts mature and differentiate into one of many cell types that make up the mucosal barrier [25]. A recent study by Mahapatro et al demonstrated that intestinal IL-33 expression is localized to the pericryptal fibroblasts during homeostasis and is increased during infection [55]. These authors have also elucidated a role for IL-33/ST2 signaling in the differentiation of stem cells in organoid culture.…”
Section: Il-33: An Alarmin In the Intestinementioning
confidence: 99%
“…These authors have also elucidated a role for IL-33/ST2 signaling in the differentiation of stem cells in organoid culture. Activation of the IL-33/ST2 pathway in epithelial progenitor cells leads to inhibition of Notch signaling and results in the differentiation of stem cells towards a secretory intestinal cell lineage [55]. These secretory cells include Paneth cells, goblet cells, and enteroendocrine cells.…”
Section: Il-33: An Alarmin In the Intestinementioning
confidence: 99%
“…[69][70][71] In contrast to Paneth cell deficiency, the cytokine IL-33 was recently reported to promote Paneth cell differentiation. 72 IL-33 and its receptor ST2 appear to both play important roles in several aspects of GVHD pathophysiology that are highly context-dependent.…”
mentioning
confidence: 99%